Early Detection of Diabetic Foot Peripheral Neuropathy With The Michigan Neuropathy Screening Instrument (Mnsi): A Scoping Review - Oper, Nunung Khairun Nissa; Kristianto, Heri; Yuliatun, Laily (Syntax Corporation Indonesia, 2023)
Background: Neuropathy is a major cause of morbidity and mortality in type 1 and 2 diabetes worldwide. The development of neuropathy and its severity increases with increasing duration of DM and poor glycemic control. Early detection of neuropathy is essential to prevent worse disease complications. Objective: to identify a simple instrument MNSI in detecting peripheral neuropathy of diabetic foot. Methods: Scoping review protocol using 5 steps of Aksey and O'Malley Framework. Inclusion criteria were published in 2016-2023, full text, English language and discussed the use of MNSI in detecting peripheral neuropathy. This article used 4 databases (Pubmed, ProQuest, and ScienceDirect) with the keywords